Competencias del tutor presencial y su incidencia en la deserción estudiantil de los alumnos de la unidad educativa a distancia “Isidro Ayora Cueva” de la ciudad de Loja, período 2012. Lineamientos alternativos - Borrero Fuentes Castro, Claudia Salomé (2013)
The present research work was oriented to a study about the tutors’ competences and the students’ desertion incidence at Unidad Educativa a Distancia Isidro Ayora Cueva of the Loja City, academic year 2012. Alternative guidelines, to face the problems that exist about the students’ desertion by mean of the scientific investigation. The methods used during the investigative process were: scientific, inductive, deductive and descriptive and as a technique the research group used the survey which was applied to the tutors and students at Unidad Educativa a Distancia Isidro Ayora Cueva. After the analysis and interpretation of the results and the corresponding discussion as a conclusion the researches can say: it exists the lack of competences, the necessary tutors knowledge and the incidence on the students’ desertion at Unidad Educativa a Distancia Isidro Ayora Cueva of the Loja City, academic year 2012. Alternative guidelines, it means that, it is pertinent to work in the process of teaching with new methods, pedagogical and psychological methods performed by the tutors with their students in order to avoid the students’ desertion, adolescents’ pregnancy, lack of material, familiar disintegration, lack of opportunities, etc. Distance education is an educative modality where students do not have to be physically in a classroom. Normally, tutors send to students the e-mails with the material to study such as: texts, videos, audio tapes, CDS that the student has to solve those exercises. The point is that in the unmotivated students to continue with their studies due to many situations. Those aspects must be taken into account for the tutor. E-learning is the developed learning with the new communicative technologies. In some cases, students have to go to the classroom to receive classes or to take exams. Finally, alternative guidelines are set up to the researched problem with the objective of contributing to the solution of the detected situation.